A Note on BKP for the Kontsevich Matrix Model with Arbitrary Potential - Borot, Gaëtan; Wulkenhaar, Raimar (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
We exhibit the Kontsevich matrix model with arbitrary potential as a BKP tau-function with respect to polynomial deformations of the potential. The result can be equivalently formulated in terms of Cartan-Plücker relations of certain averages of the Schur -function. The extension of a Pfaffian integration identity of de Bruijn to singular kernels is instrumental in the derivation of the result.